Implementasi Jaringan Hotspot Dan Bandwidth Management Dengan Menggunakan Mikrotik Routers Pada Café Roemah Kedua - Sufajar Butsianto; Anisah Purnamasari (Teknik Informatika, Universitas Pelita Bangsa, 2021)
The The research objective was to analyze and implement network hotspots and bandwidth management at the Second Café House, so that the Café can provide microtic-based hotspot facilities, evenly distribute bandwidth on hotspot networks to each customer and limit bandwidth usage according to the time stated on the voucher package. The research methods included the analysis method, namely by conducting a survey of the system that is running and the study of literature, the design method of network topology by selecting network devices to be used and configuration on each network device used, testing new networks, and maintenance activities ( bandwidth traffic monitoring). The results of the research obtained are the implementation of the design of network hotspot topology and bandwidth management using RouterOS Microtics optimize the performance of hotspot networks and maximize bandwidth on hotspot networks. The conclusion of this study is that by using RouterOS Microtics on hotspot networks, internet cafes can limit the bandwidth usage of customers based on the voucher package that has been made and there is no attraction in attracting bandwidth between customers due to equal bandwidth distribution. Keywords: RouterOS Microtics, Hotspot, Bandwidth Management